Analysis of Changes in Corneal Topography after 27-Gauge Transconjunctival Microincision Vitrectomy Combined with Cataract Surgery - Tomoyuki Watanabe; Tamaki Gekka; Akira Watanabe; Tadashi Nakano (Journal of Ophthalmology)
Purpose. To investigate changes in the corneal shape before and after vitrectomy, over a period of time, using a 27-gauge system. Methods. Forty-five eyes underwent a combination of cataract surgery and vitrectomy. The surgeries were performed using a 27-gauge transconjunctival vitrectomy system, in which the corneal topography could be performed up to three months after the surgery. The surgeries were performed for an epiretinal membrane in 11 eyes, a macular hole in 14 eyes, and rhegmatogenous retinal detachment in 20 eyes. All of the surgeries were performed by the same surgeon, and in all cases, a 4-port 27-gauge vitrectomy device was used. Cataract surgery in all patients was performed with a 2.4 mm corneoscleral incision at 11 o’clock. The surgeries were performed without suturing the operative wound in all cases. Corneal topography was performed using a TMS-4 topographer (Tomey Corporation, Tokyo, Japan). The examinations were performed the day before and 1 day, 1 week, 1 month, and 3 months after the surgery. The results of corneal topography for the spherical, regular astigmatic, asymmetric, and high-order irregular astigmatic components were compared before and after surgery. Results. No significant differences were seen in any of the components in the epiretinal membrane group, but significant differences were seen in the asymmetric components and the high-order irregular astigmatic components between the macular hole and rhegmatogenous retinal detachment groups (p<0.05). There were no significant changes in intraocular pressure on any measurement time in the postoperative period compared to preoperative intraocular pressure. Conclusion. Irregular astigmatism was seen after surgery when 27-gauge vitrectomy with a 4-port system was performed together with cataract surgery with a 2.4 mm incision.